Moral Economy of Death: Religious Legitimacy and Social Obligations in Ta‘ziyah Practices in Indonesia - Paelani Setia; Muhammad Ikhlas Rosele; Rika Dilawati (Parahyangan Catholic University, 2026)
This study examines ta‘ziyah practices in rural West Bandung Regency, Indonesia, through the lens of moral economy to explain how economic obligations within death rituals become legitimized, reproduced, and accepted as integral components of religious practice. This study employs a qualitative approach through participant observation and in-depth interviews with bereaved families, kiai, mosque administrators, community leaders, and local residents involved in ta‘ziyah practices. Drawing on James C. Scott’s moral economy perspective, this study demonstrates that ta‘ziyah functions not only as an expression of piety and social solidarity but also as a moral-economic system that positions bereaved families as the primary providers of ritual resources. Religious legitimacy, which emerges through the authority of kiai, the discourse of sedekah almarhum/almarhumah (charity on behalf of the deceased), and local social norms, transforms religious recommendations into social obligations that community members find difficult to refuse. This ritual governance subsequently reproduces unequal distributions of obligations and increases the economic and social vulnerability of bereaved households. These findings highlight the need for critical reflection on death ritual practices so that social solidarity does not evolve into an additional burden for vulnerable groups. This study contributes to the literature by extending moral economy theory into the study of death rituals and local Islam in Indonesia.